Enterococcus casseliflavus and Enterococcus gallinarum as causative agents of spontaneous bacterial peritonitis - Narciso-Schiavon, Janaína Luz; Borgonovo, Ariane; Marques, Paula Couto; Tonon, Débora; Bansho, Emilia Tiemi Oshiro; Maggi, Dariana Carla; Dantas-Corrêa, Esther Buzaglo; Schiavon, Leonardo de Lucca (Annals of hepatology, 2015)
Infection by multidrug resistant bacteria is arousing as a relevant issue among hospitalized subjects and is of particular interest in patients with cirrhosis given the frequent use of broad spectrum antibiotics and their altered immune response. We report the first case report of spontaneous bacterial peritonitis (SBP) caused by Enterococcus casseliflavus and the sixth case of SBP caused by Enterococcus gallinarum.